Pengaruh Kurs Dollar Amerika Serikat, Inflasi, dan Harga Ekspor Terhadap Nilai Ekspor Pakaian Jadi Indonesia - Eka Yanti, Ni Wayan Susi; Sudirman, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 3, Maret 2017 (pp. 286-471), 2017)
Textile commodities is one of the leading commodity exports at the same time is a commodity that provides employment opportunities and contribute substantially to the total non-oil exports in Indonesia. One textile commodities exported by Indonesia is Clothes so. The purpose of this study was to determine the effect of the US dollar exchange rate, inflation and the export price to the value of apparel exports Indonesia 1995-2014 period simultaneously or partially. As well as to analyze the dominant variables that affect the value of apparel exports Indonesia. Multiple linear regression analysis used in this study. The results showed that simultaneous variable US dollar exchange rate, inflation and export prices significantly influence the value of apparel exports Indonesia period 1995-2014. Variable US dollar exchange rate and export prices partially positive and significant, while the variable inflation and significant negative effect on the value of apparel exports of Indonesia in 1995-2014. In the analysis of the export price variables have a dominant influence on the value of apparel exports Indonesia.
Keywords: Apparel Exports; The United States Dollar Exchange Rate; Inflation; Export Prices.